Modeling lexical abilities of heritage language and L2 speakers of Hebrew and English in Israel and the United States: a network approach - Fridman, Clara; Livni, Adina; Bar On, Sagit; Meir, Natalia (Frontiers in Psychology, 2024)
Introduction This paper examines the productive vocabulary skills of five groups of English-Hebrew bilinguals in Israel and the United States. The juxtaposition of these five groups allows us to simultaneously compare performance across dominance profiles, acquisition contexts (L2 learned in school, HL maintained at home, immigration and immersion), and countries (Israel and the USA). Methods A total of 185 participants took part in study: Hebrew-dominant heritage English speakers, Hebrew-dominant L2-English speakers, English-dominant heritage Hebrew speakers, and English-dominant L2-Hebrew speakers in the US and in Israel. They were all administered the MINT assessment in both languages, as well as background questionnaires. We then employ network modeling based on a secondary data analysis of background questionnaires to consider how each group’s lexical proficiency ties in to reported input factors. Results and discussion The MINT results indicate clear language dominance in all the groups except Hebrew-dominant heritage English speakers, who show balanced proficiency in both their languages. The network models indicate key distinctions between the groups as a function of linguistic context, and we assess our findings in the context of recent work on quantifying the bilingual experience.